Pentingnya Pemahaman Konsep Geogebra dalam Pembelajaran Matematika - Dian Fatma Diva; Juli Andriyani; Sakdiah Aini Rangkuti; Melani Prasiska; Talitha Eriliyah Wardhana Lumban Tobing; Abdul Razaky Irani; Risna Mira Bella Saragih (Journal on Education, 2023)
From the research results, there are data indicating that students' learning abilities can be further enhanced by introducing smart games and integrating the best recommended approach to improve student achievement in various mathematical topics is the use of technology in the teaching and learning process. Methods The data mining approach can be further enhanced to generate knowledge and provide intelligent assistance to students. Real and larger data sets can be simulated to analyze the behavior of the recommended data mining approach (causar). The purpose of this study to see is to see the importance of understanding the concept of Geogebra for learning Mathematics. The result of this research is that GeoGebra enhances lessons and activity design has the advantage to inspire students towards their learning and hence to improve their academic achievement GeoGebra has been found to be an important tool in teaching and learning mathematics in secondary and higher education.